Judicial Power as a Material Content of The 1945 Constitution in The Perspective of its Development and Objectives - Punu, Doni; Dilapanga, Ridwan; Daud, Tiara Namira Oktaviana (Universitas Negeri Gorontalo, 2023)
The power of the judiciary as one of the content materials in the written constitution of a legal state is inseparable from the conception of the trias politica. It is intended to ensure the independence of judges in shaping the law through their rulings as well as to prevent abuse of power. In this case, it is important to prove that the intention is in accordance with the substance of the judicial power in the content of the 1945 Constitution. On this basis, this study is limited to two subjects, namely about the extent to which the background of judicial power is the content material in the 1945 Constitution and the position of judicial power as content material in the 1945 Constitution. Both of these things will be analyzed normatively using a statutory approach and a historical approach. The final results of this study show that despite the change of government regime, the form of the state until the amendment of the 1945 Constitution, judicial power remained an important and fundamental content in the 1945 Constitution. One of the processes of legal formation can occur in the judiciary through judges' decisions, therefore the substance of the changes in the 1945 Constitution aims to strengthen the independence of judicial power as well as strengthen the principle of separation of powers mainly in the judicial power section as a form of checks and balances.